Galaxies - World Book, Inc (Chicago World Book, 2010)
An introduction to galaxies with information about their formation and characteristics. Includes diagrams, fun facts, glossary, resource list, and index"--Provided by publisher
Includes index
Hurg
5 8
Keywords: Galaxies -- Juvenile literature